PROTECTING INDONESIA'S SOVEREIGNTY THROUGH CIVIC ENGAGEMENT IN THE TEMAJUK VILLAGE BORDER AREA - Thomy Sastra Atmaja; Shilmy Purnama; Jagad Aditya Dewantara; Muhamad Supriadi (The Republic of Indonesia Defense University, 2022)
This study aims to determine the involvement of the society in maintaining and protecting the sovereignty of the Border region in Temajuk. Camar Bulan Subvillage, Temajuk Village, is an area in West Kalimantan Province that is directly adjacent to Malaysia. Under these conditions, this area was once claimed by the state of Malaysia and had become a concern of the public or government. The claim was made by the Malaysian state by establishing 2 lighthouses in the waters of Camar Bulan Sub village. Fortunately, the case was resolved through peace negotiations between countries. After the claim, the community responded to this problem by voluntarily involving themselves in maintaining the boundaries of state sovereignty. The approach used is qualitative and descriptive method. Data sources of the research consisted of Village Officials (Village heads), border guard volunteers (border stake guard officers and border youth), and the people living in the Temajuk border area of West Kalimantan. Data analysis techniques include data collection, data reduction, data presentation, dan conclusion/verification. The results obtained include: (1) society involvement in the Indonesia-Malaysia border has been actively involved in various social and political activities as a form of defending the country; and (2) supporting factors in maintaining the sovereignty of Indonesia's territory in the border areas, namely public awareness is high enough to maintain the sovereignty of the Indonesian border include the existence of the 1945 Constitution of the Republic of Indonesia, society awareness to maintain sovereignty as the highest authority holder, society cooperation with various authorities in maintaining the Unitary State of the Republic of Indonesia.Â